Analysis of Public Service Quality at the Sirimau Sub-District Office in Ambon City - Almahdali, Humairah; Sakir, Ahmad Rosandi (Teras Kampus, 2024)
This research aims to understand the evaluation of public service quality at the Sirimau Sub-District Office in Ambon city, which will be analyzed using the Servqual Method. The research method used in this analysis is qualitative descriptive. This research will be conducted at the Sirimau Sub-District Office, Ambon City, Maluku. The research informants consist of 10 people from various elements, including sub-district office employees, sub-district government elements, and community members receiving services from the sub-district office. This research reveals several key aspects that influence the quality of public services at the Sirimau Sub-District Office. Firstly, reliability is the main focus, which includes the implementation of tasks according to standards and proficiency in using aids. Furthermore, the responsiveness of employees in responding to the needs and complaints of the community is a determinant factor of user satisfaction. The importance of insurance or guarantees in providing protection and certainty to the community is also revealed in this research. Additionally, the empathetic, friendly, and appreciative attitude of the officers helps build a good relationship with the community. Lastly, in terms of physical evidence, although most indicators are considered good, There are still issues regarding the comfort of the service area that need to be addressed promptly